External Sector Report, July 2018 : Tackling Global Imbalances amid Rising Trade Tensions. (External Sector Report; External Sector Report, 2018)
The External Sector Report presents a methodologically consistent assessment of the exchange rates, current accounts, reserves, capital flows, and external balance sheets of the world's largest economies. The 2018 edition includes an analytical assessment of how trade costs and related policy barriers drive excess global imbalances.